Modulation of enso teleconnections by the Indian Ocean dipole over South America during austral spring - Osman, Marisol (2025)
The El Niño–Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) are key modes of tropical variability with strong impacts across the Southern Hemisphere. Although ENSO is known to influence South American precipitation and temperature anomalies during austral spring (SON), the role of the IOD in modulating these patterns has received less attention. This study investigates how the IOD modulates the atmospheric circulation and surface climate response in South America to ENSO during SON.